Correlation of Pelvimetry and Age Based on 3D CT Scan Examination - Teuku Fadlian Syah; Mirna Muis; Rafikah Rauf; Andi Alfian Zainuddin (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: The radiological pelvimetry is a measurement by using 3D Computed Tomography (CT) which will pelvis shape. The Pelvimetry size is not always constant, but it can change due to several factors, among others are age, heredity, number of pregnancies. The age changes can be related to the adaptation to the sitting position and compensation of the spino-pelvic balance change having the impact on the walking style stability. Purposes: The research aims to analyze the correlation between the pelvimetry and age based on CT scans 3D examination of patients from January 2021 to April 2022 in General Central Hospital of Dr. Wahidin Sudirohusodo, Makassar Indonesia. Methods: The research used the cross sectional design with Spearman correlation test. Results: There were 105 samples involved in the research. The most age group ranged from 40 to 49 years old with the percentage of 32.4%. The average size of the conjugate vera is 11.49 cm (SD±0.95), obstetric conjugate is 11.46 cm (SD±0.92), diagonal conjugate is 12.27 cm (SD±0.87), interspinous diameter is 10 .15 cm (SD±0.95), intertuberous diameter is 10.58 cm (SD±1.02), and transverse diameter is 11.99 cm (SD±0.88). The research result indicates that the conjugate vera, obstetrical conjugate, diagonal conjugate, and intertuberous diameter have the correlation with the age (p<0.05), while the interspinous diameter and transverse diameter do not indicate the correlation (p>0.05). Conclusions: The conjugate obstetrics and conjugate diagonalis have weak correlation, while the moderate correlation strength occurs in the intertuberous diameter.